The Student’s Perception of Using ChatGPT for EFL Students - Rizki Novia Darma; Abdul Syahid; Fatma; Ayu Putriana Lestari; Ahmad Basahil; Rini Listiya Ningrum (PT. Padang Tekno Corp, 2023)
ChatGPT has attracted considerable media and academic attention as one of the latest developments. It has the ability to generate answers to questions and perform other language-related tasks with exceptional accuracy. This is due to its extensive training set, which closely resembles human-produced texts. Many researchers consider ChatGPT to be an interesting tool for improving students' language and knowledge skills, as well as their problem-solving and communication skills. The study discussed some perceptions of the merits of ChatGPT on English student with each representative answering or filling a questionnaire containing their views or responses to ChatGPT conversations using a quantitative descriptive method. It is hoped that the study can learn how English education students feel using small talk, whether it is having a good effect on their performance or whether it is adversely affecting their performance in college. The results of correlation analysis show patterns of relationships between different variables. There is no linear relationship between the level of agree and strongly disagree, but there is a strong and negative correlation between the level of disagree and strongly agree. meanwhile, a strong positive relationship was observed between neutral and strongly disagree levels.